Environmental risk assessment and protection measures due to dewatering during construction of Wangfuzhuang Metro Station, Jinan, China - G. Li; B. Hu; L. Lu; J. Chen (International Association of Lowland Technology, 2019)
Jinan is famous due to its spring group with rich groundwater resources. The groundwater system should be protected during the construction of the metro system. This paper presents a case study of the environmental risk assessment due to dewatering and recharges during the construction of Wangfuzhuang Metro Station, Jinan, China. The Fuzzy Analytic Hierarchy Process (FAHP) is employed to evaluate the impact on the environment. Moreover, based on Darcy’s law, and water inflow calculations for a submersible full well and water level line equation under the coupling action of a submersible full dewatering-recharge well group, the dewatering and recharge schemes of the deep foundation pit excavation are designed. Both results from numerical simulation and site survey show that dewatering and recharging at the Jinan R1 line site were effective in environmental protection.